ANALISIS SISTEM INFORMASI AKUNTANSI ZAKAT, INFAK, DAN SEDEKAH DI BAZNAS KOTA BUKITTINGGI - Nur Halimah Djamta; Awaluddin (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this research is to analyze the zakat, infak, and sedekah financial statements prepared by BAZNAS Bukittinggi City using PSAK 109 and to learn more about the accounting information system that handles these funds. The author's goal in employing a qualitative approach in this study is to provide an explanation of the phenomenon through the analysis of data collected through detailed descriptions of observations, interviews, and documentation. Findings from the study's analysis of BAZNAS Bukittinggi City's zakat, infak, and sedekah accounting information system stem from the system's efficient and effective implementation, which in turn stems from the frequent occurrence of incorrect printed output due to data entry mistakes. While BAZNAS Bukittinggi City's zakat, infak, and sedekah accounting information system satisfies the requirements of PSAK 109, the data entry process is still manual, leading to inefficiencies.